2016
DOI: 10.18805/lr.v0iof.10761
|View full text |Cite
|
Sign up to set email alerts
|

Stability for disease, genotype x environment interaction for yield andits components in pigeonpea [Cajanus cajan (L.) Millsp.]

Abstract: The material for study of genotype x environment (G x E) interaction comprised of 23 genotypes, which were tested in four environments, during kharif-2012 and 2013 at two locations in Agricultural Research Station, Kalaburagi and Raddevadgi located in north eastern dry zone (Zone 2) of Karnataka. The experiment was laid out in lattice design with two replications. Highly significant differences among genotypes were observed for all the characters except number of pods per plant and yield per plant. Environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…However, when the environment and genotype have different polarities, an undesirable interaction results. The results obtained from our investigation align with the recorded findings ( Kaya et al., 2002 ; Muniswamy et al., 2021 ; Reddy et al., 2023 ; Kona et al., 2024 ). The results of this study provide empirical support for the implementation of AMMI 2, showing that the AMMI model demonstrates a satisfactory degree of consistency with the gathered data.…”
Section: Discussionsupporting
confidence: 93%
“…However, when the environment and genotype have different polarities, an undesirable interaction results. The results obtained from our investigation align with the recorded findings ( Kaya et al., 2002 ; Muniswamy et al., 2021 ; Reddy et al., 2023 ; Kona et al., 2024 ). The results of this study provide empirical support for the implementation of AMMI 2, showing that the AMMI model demonstrates a satisfactory degree of consistency with the gathered data.…”
Section: Discussionsupporting
confidence: 93%
“…FPVS trials from other states and multi-location trials revealed significant GEI effects, indicating a differential response of genotypes in different environments. Significant genotype, environment, and GEI in pigeonpea for grain yield were reported earlier by Muniswamy et al [59] and Arunkumar et al [60]. For instance, FPVS trials in Andhra Pradesh, at Guntur and Prakasam, LRG 105 followed by LRG 160 while at Kurnool, LRG 52 followed by LRG 160 but across the locations, LRG 160 followed by LRG 105 revealed a significantly higher grain yield.…”
Section: Discussionsupporting
confidence: 49%
“…The objective of the testing would be to identify the best performing varieties in each of the growing environments for farmer recommendations. Environments differ in their ability to support different genotypes and environments it is refereed to edaphic, climatic and management conditions done by the farmer depending on the growing environment in which the farmer produces a crop (Mohamed, 2013, Muniswamy et al, 2017. Years also differ in their ability to support a crop, the reason why they are tested as rain fed in multi-location trials (Gauch, 1988).…”
Section: Introductionmentioning
confidence: 99%